Global Trends in Social Work Research: A Bibliometric Analysis of the Last 10 Years Using Bibliometric and VOSviewer - Yongki Sostenes Yesyan; Eko Priyo Purnomo; Rahmawati Husein (Universitas Pendidikan Ganesha, 2026)
In the past decade, social transformations such as pandemics, inequality, migration, and digitalization have significantly influenced the growth of social research. Research on the dynamics of public life in international databases is still lacking. The purpose of this study is to analyze trends in social work publications from 2015 to 2024 based on 43 journal articles specifically indexed using Scopus data. used with the help of Biblioshiny and VOSviewer software to analyze national productivity growth, scientific publications, collaboration networks, and key co-occurrence patterns. The study findings show that there has been an increase in the number of publications since 2020, with an initial focus on COVID-19 and mental health issues before shifting to social safety, social intervention, child safety, and policy issues. There has been a significant increase in the number of publications since 2020, with an initial focus on COVID-19 and mental health issues before shifting to social safety, social intervention, and child safety. The three main themes identified by the network analysis are professional and work-related dimensions, child welfare identified by families, and social and personal factors. The network analysis covers professional and work-related dimensions, as well as child and family welfare and social and personal factors. Based on the number of publications in the analyzed dataset, Indonesia has the highest contribution, even though the intensity of its international collaboration is relatively low. This needs to be carefully considered because the database and index structure can affect national representation. This study highlights the evolution of themes found in the Scopus corpus and emphasizes the importance of international collaboration and cross-database analysis to obtain more comprehensive information about the development of social work research around the world.